2020
DOI: 10.1016/j.ydbio.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

CFAP43 modulates ciliary beating in mouse and Xenopus

Abstract: Malfunctions of motile cilia cause a variety of developmental defects and diseases in humans and animal model organisms. Defects include impaired mucociliary clearance of the airways, sperm immotility, hydrocephalus and organ laterality. Here, we characterize the evolutionary conserved Cfap43 gene by loss-of-function experiments in the mouse and the frog Xenopus laevis. Cfap43 is expressed in tissues carrying motile cilia and acts as a target gene of the transcription factor FOXJ1, which is essential for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 56 publications
(78 reference statements)
0
17
1
Order By: Relevance
“…6F). This differs from Tll1 (Ikegami et al, 2010) and Cfap43 mutants (Rachev et al, 2020), in which an increase in beating frequency was associated with reduced cilia-generated flow. Although loss of CFAP206 clearly affects ciliary beating in respiratory epithelium, it remains to be seen how this relates to mucous accumulation.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…6F). This differs from Tll1 (Ikegami et al, 2010) and Cfap43 mutants (Rachev et al, 2020), in which an increase in beating frequency was associated with reduced cilia-generated flow. Although loss of CFAP206 clearly affects ciliary beating in respiratory epithelium, it remains to be seen how this relates to mucous accumulation.…”
Section: Discussioncontrasting
confidence: 58%
“…To address potential changes in ciliary beating of cfap206 crispants, motility of epidermal MCCs was analysed in high-speed time-lapse videos recorded from wild-type and crispant larvae at stage 32 (Movie 1). Ciliary beat frequencies were calculated as previously reported (Rachev et al, 2020) and found to be significantly elevated, from 22.5 Hz in wild type to 24.5 Hz in sgRNA1 crispants and 26.5 Hz in sgRNA2 crispants ( Fig. 4Aa; Table S3).…”
Section: Functional Analysis Of Cfap206 During Embryonic Development mentioning
confidence: 64%
See 3 more Smart Citations